2012
DOI: 10.3109/00207454.2012.694936
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Rate of Recurrence of Epilepsy after Therapy Discontinuation in 2-Year Seizure-Free Epileptic Patients

Abstract: As our findings suggest, type of epilepsy, multidrug therapy, abnormal electroencephalography before discontinuation, and abnormal brain computed tomography scan are factors that influence the risk of recurrence after therapy discontinuation. It is essential for the physician to take these factors into account and weigh the risk of recurrence against the benefits of therapy discontinuation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 16 publications
2
6
0
Order By: Relevance
“…Several recent studies have investigated the relationship between seizure relapse and the number of ASMs in patients with ASM withdrawal, but there has been no consistent conclusion. Our results demonstrated that patients treated with polytherapy had a higher seizure relapse risk than those with monotherapy (HR = 2.152, 95% CI = 1.350-3.428), which was in line with previous studies (23,(30)(31)(32). We also found that the risk of early recurrence (within the first 6 months) in polytherapy-treated patients was significantly higher than that of the monotherapy group (22.6 vs. 9.6%, p = 0.018).…”
Section: Discussionsupporting
confidence: 92%
“…Several recent studies have investigated the relationship between seizure relapse and the number of ASMs in patients with ASM withdrawal, but there has been no consistent conclusion. Our results demonstrated that patients treated with polytherapy had a higher seizure relapse risk than those with monotherapy (HR = 2.152, 95% CI = 1.350-3.428), which was in line with previous studies (23,(30)(31)(32). We also found that the risk of early recurrence (within the first 6 months) in polytherapy-treated patients was significantly higher than that of the monotherapy group (22.6 vs. 9.6%, p = 0.018).…”
Section: Discussionsupporting
confidence: 92%
“…Predictors for seizure recurrence after a minimum remission of 2 years in patients with a history of epilepsy include AED polytherapy, having experienced seizures after the start of AED treatment, longer duration of active epilepsy, and having an abnormal electroencephalogram (EEG) [58,62,63]. Especially, a history of primary or secondary generalized tonic-clonic seizures is found to be a risk factor for seizure recurrence after withdrawal, although some studies report that focal seizures are an independent predictor for relapse as well [6,59,62,64]. Moreover, the risk of seizure recurrence is reported to depend on the specific AED being withdrawn, with a particularly high risk of relapse after discontinuation of phenobarbital [65].…”
Section: Withdrawal In Patients Treated With Aeds Onlymentioning
confidence: 99%
“…A higher risk of seizure recurrence in patients with focal epilepsy might be related to an underlying etiology. In the larger withdrawal studies in patients with epilepsy treated with AEDs only, presence of an underlying neurological condition or abnormalities on computed tomography scan has been associated with a higher relapse risk after AED discontinuation [6,64]. According to the guidelines of the Italian League Against Epilepsy, a documented etiology of seizures is of limited relevance when deciding to discontinue AEDs, if this is the only negative prognostic factor [62].…”
Section: Withdrawal In Patients Treated With Aeds Onlymentioning
confidence: 99%
See 1 more Smart Citation
“…In patients with non-tumour-related epilepsy AEDs are generally discontinued some time after successful epilepsy surgery [ 18 ],[ 27 ],[ 28 ]. AED withdrawal following temporal lobe resection in patients with refractory non-tumoural epilepsy eventually leads to seizure freedom without use of AEDs in 77% of patients [ 29 ].…”
Section: Introductionmentioning
confidence: 99%